III-V dielectric metasurfaces: enhanced nonlinearities and emission control - Liu, Sheng; Vaskin, Aleksandr; Vabishchevich, Polina; Addamane, Sadhvikas; Keeler, Gordon A.; Reno, John; Yang, Yuanmu; Staude, Isabelle; Balarishnan, Ganesh; Sinclair, Michael B.; Brener, Igal (Optics InfoBase Conference Papers, 2017)
Using III-V dielectric metasurfaces, we experimentally demonstrate resonantly enhanced harmonic generations up to the 4th order. Moreover, we observe large enhancements and spectral tailoring of the photoluminescence of quantum dots embedded inside dielectric metasurfaces.
CRIS-Team Scopus Importer:2023-04-20